RANCANG BANGUN DESAIN 3D MODEL DAN PERAKITAN MESIN PERAJANG SINGKONG DENGAN TENAGA MOTOR ¼ HP KAPASITAS 30 KG/JAM - Gumilar, Cahya; Saleh, Agus (Jurnal Mahasiswa Terapan, 2024)
This research was motivated by the increasing number of Micro, Small and Medium Enterprises (SME) that sell snacks, experiencing difficulties in dealing with consumers because they prepare snack ingredients that must be processed first, one of which is processing cassava by chopping it, namely making it into cassava chips. With that, to simplify the process of chopping cassava chips and increase the added value and efficiency of the process of making cassava chips, a Cassava Chopper Machine was created. Cassava Chopper Machine is a machine that has a knife with sharp edges for cutting. This cassava chopping machine has a back and forth movement mechanism, so it can cut cassava to a size that has been adjusted for thickness. The results of stretching this machine will produce a harmonious shape and size, so that when the frying stage is carried out the results will be right and good. This chopping machine is a good solution to replace the manual chopping process.